2022
DOI: 10.1155/2022/6084732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self‐Transcendence Theory Combined with Comprehensive Nursing Intervention under Tumor Nutrition Education on Symptom Improvement, Nutritional Status, and Positive Psychology of Elderly Patients with Gastric Cancer

Abstract: Objective. To explore the value of self-transcendence theory combined with comprehensive nursing intervention under oncological nutritional education on improvement in symptoms, nutritional status, and positive psychology of elderly patients with gastric cancer (GC). Methods. A total of 98 elderly patients with GC in the First Affiliated Hospital of Xi’an Jiaotong University from January 2021 to December 2021 were enrolled. All these patients were arbitrarily assigned into the observation group (n = 49) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The diagnosis and treatment of GC might impact the psychological condition of patients[ 24 ]. Some interventions, such as proper social support[ 25 ] and multidisciplinary cooperative continuous nursing[ 26 ], could relieve the depression of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of GC might impact the psychological condition of patients[ 24 ]. Some interventions, such as proper social support[ 25 ] and multidisciplinary cooperative continuous nursing[ 26 ], could relieve the depression of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al also pointed out that comprehensive nursing intervention is beneficial to improving symptoms and nutritional status, controlling the incidence of malnutrition, reducing anxiety and depression, and assisting surgery. 25 Nonetheless, there are some limitations in this study. First of all, insufficient samples are included in this study, which may lead to biased statistical analysis results.…”
mentioning
confidence: 89%
“…Studies have found that the application of a combined intervention model of psychological intervention combined with nutrition and exercise interventions is significant for tumor patients. 52,53 Therefore, joint symptom-psychological interventions focusing on symptoms should be considered for patients with PLC after hepatectomy to reduce the level of anxiety/depression in patients. In the clinical setting, it is recommended that medical staff pay close attention to the presence and severity of anxiety/depression in patients with PLC after hepatectomy, in addition to symptom burden.…”
Section: Associations Among Symptom Burden Resilience and Anxiety/dep...mentioning
confidence: 99%